PENGARUH ORGANIZATIONAL CITIZENSHIP BEHAVIOUR, PERCEIVED ORGANIZATIONAL SUPPORT, DAN MODERASI KUALITAS PELAYANAN REKANAN ERP TERHADAP KINERJA PEMGGUNAAN ERP - Thomas Dwi Susmantoro (Universitas Multimedia Nusantara, 2020)
The usage of Enterprise Resource Planning (ERP) as an effort of the company to improve competitiveness through the implementation of integrated system and the utilization of information resources, demands the participation of stakeholders in ensuring the successful achievement company’s objective. Unlike previous research, in this study seeks to examine aspects that the involvement of all stakeholders both inside and outside the organization of the company that can influence the usage of ERP in the company. It identified the influence of Organizational Citizenship Behaviours (OCB), Perceived Organizational Support (POS) and moderation of the quality of partner services to the performance of ERP usage. This research was conducted on 87 erp executives, managers and users from 46 companies in Indonesia. It found the positive influences of OCB, PDO and moderation of the quality of partner services on the performance of ERP usage. The result of the research explains how companies can improve the performance of ERP usage which ultimately impacts the company's competitiveness. Key Words: ERP, Organizational Citizenship Behaviours (OCB), ERP Usage, Perceived Organizational Support, Quality Service